PENGEMBANGAN MODEL LATIHAN PERMAINAN KATA (JURUS) PADA CABANG OLAHRAGA KARATE - Senani, A. Risky Kirana; Purwanto, Didik; Rejeki, Hendriana Sri (Jurnal Porkes, 2025)
This study aims to develop a kata training model in karate through game-based methods to enhance technical skills, motivation, and self-confidence among beginner athletes (kohai). Based on observations and questionnaires conducted at INKANAS Dojo in Donggala Regency, several issues were identified such as low athlete motivation, monotonous training routines, and lack of engaging learning methods. To address these challenges, the researcher designed a structured and enjoyable game-based training model tailored for children aged 8–13 years. This research employed a Research and Development (R&D) approach, adapting the eight-step development model by Borg and Gall. Validation was conducted by subject matter, media, and game experts, while product trials involved a total of 24 kohai in small and large-scale testing. Results showed high feasibility and effectiveness, with an average validity score of 93.33%, motivation improvement of 96%, and kata technique mastery reaching 92%. The developed model enriches training variation and significantly improves karate learning quality. The resulting training guidebook can be widely used by coaches across dojos as an applicable and fun training tool, supporting the holistic development of athletes' character and skills.